Cardiac Dysfunction in Neonatal HIE Is Associated with Increased Mortality and Brain Injury by MRI - Altit, Gabriel; Bonifacio, Sonia L.; Guimaraes, Carolina V.; Bhombal, Shazia; Sivakumar, Ganesh; Yan, Beth; Chock, Valerie; Meurs, Krisa V. (American Journal of Perinatology, 2021)
Objective Describe the association between cardiac dysfunction and death or moderate-to-severe abnormalities on brain magnetic resonance imaging (MRI) in neonates undergoing therapeutic hypothermia for hypoxic ischemic encephalopathy (HIE).Study Design Retrospective study in neonates with moderate or severe HIE undergoing therapeutic hypothermia between 2008 and 2017. Primary outcome was death or moderate-to-severe brain injury using the Barkovich score. Conventional and speckle-tracking echocardiography measures were extracted from available echocardiograms to quantify right (RV) and left (LV) ventricular functions.Results A total of 166 newborns underwent therapeutic hypothermia of which 53 (36.5%) had echocardiography performed. Ten (19%) died prior to hospital discharge, and 11 (26%) had moderate-to-severe brain injury. There was no difference in chronologic age at echocardiography between the normal and adverse outcome groups (22 [±19] vs. 28 [±21] hours, p = 0.35). Cardiac findings in newborns with abnormal outcome included lower systolic and diastolic blood pressure (BP) at echocardiography (p = 0.004) and decreased tricuspid annular plane systolic excursion (a marker of RV systolic function; p = 0.01), while the ratio of systolic pulmonary artery (PA) pressure to systolic BP indicated isosystemic pressures (>2/3 systemic) in both groups. A multilogistic regression analysis, adjusting for weight and seizure status, indicated an association between abnormal outcome and LV function by longitudinal strain, as well as by ejection fraction.Conclusion Newborns who died or had moderate–to-severe brain injury had a higher incidence of cardiac dysfunction but similar PA pressures when compared with those who survived with mild or no MRI abnormalities.Key Points
Keywords: hypoxic ischemic encephalopathy; brain injury; cardiac dysfunction; speckle tracking echocardiography; therapeutic hypothermia